Stabilization-free Virtual Element Method for 2D second order elliptic equations - Berrone, Stefano; Borio, Andrea; Fassino, Davide; Marcon, Francesca (Computer methods in applied mechanics and engineering, 2025)
In this work, we present and analyze a Stabilization-free Virtual Element high order scheme for 2D second order elliptic equation. This method is characterized by the definition of new polynomial projections that allow the definition of structure-preserving schemes. We provide a necessary and sufficient condition on the polynomial projection space that ensure the well-posedness of the scheme and we derive optimal a priori error estimates. Several numerical tests assess the stability of the method and the robustness in solving problems characterized by anisotropies. •Virtual Element method without an arbitrary stabilization.•Structure preserving bilinear form for 2D second order elliptic equations.•Well-posedness analysis.•Algorithm for the computation of coercive polynomial projection.•Numerical tests assessing local coercivity on several polygons, and good performance on anisotropic diffusion problems.